Agronomic management on the yield and quality of coffee (Coffea arabica) Castillo variety in Nariño, Colombia - Muñoz-Belalcazar, Johanna Alixa (2021)
Introduction. In recent years the area and production of coffee has increased in Nariño, but its sustainability and profitability have been affected by various factors. Taking advantage of quality attributes could be an alternative to improve the economic activity. Objective. To analyze the incidence of agronomic management of the Castillo variety coffee production system on the yield and quality of the bean in the Nariño department. Materials and methods. The work was developed during 2018-2019 in four municipalities of the department of Nariño, Colombia. With sixty production units (UPC) with Castillo variety coffee. A mixed instrument was designed to capture information in farms and in situ variables on yield and quality, using protocols of the Specialty Coffee Association of America (SCAA) and the Federacion Nacional de Cafeteros (FNC). Results. 41.6 % of the UPCs had farms above 1700 meters above sea level, 46.6% were associated with forest species, 33.3 % with fruit trees or musaceae and 20 % with free exposure. The histogram of eigenvalues, allowed the selection of five factors that explained the 52.69 % of variability, the contributing variables were related to: type of fertilizer, frequency, dose of organic fertilizer, and density. The classification analysis allowed the formation of four groups, the fourth with the highest number of UPC (35) belonged to the western zone, used planting densities >5500 plants/hectare and combined chemical and organic fertilizers. Conclusions. Mixed systems with coffee under shade prevailed in their majority for the productive system studied, in such a way that they did not derive in the composition of differential groups, as there was with the variability in planting densities, use of organic fertilizer and fractionation of fertilization. These agronomic management variables influenced the obtaining of differences for the yield and marketable bean quality.